2019
DOI: 10.1103/physrevb.99.024430
|View full text |Cite
|
Sign up to set email alerts
|

Profile approach for recognition of three-dimensional magnetic structures

Abstract: We propose an approach for low-dimensional visualisation and classification of complex topological magnetic structures formed in magnetic materials. Within the approach one converts a three-dimensional magnetic configuration to a vector containing the only components of the spins that are parallel to the z axis. The next crucial step is to sort the vector elements in ascending or descending order. Having visualized profiles of the sorted spin vectors one can distinguish configurations belonging to different ph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 31 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…17. It is also not limited by two-dimensional case, the profile procedure we used for preprocessing magnetization data gives reliable classification results in the static case for three-dimensional magnets with Dzyaloshinskii-Moriya interaction 9 . The generalization power of the network can be increased by adding more hidden neurons layers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17. It is also not limited by two-dimensional case, the profile procedure we used for preprocessing magnetization data gives reliable classification results in the static case for three-dimensional magnets with Dzyaloshinskii-Moriya interaction 9 . The generalization power of the network can be increased by adding more hidden neurons layers.…”
Section: Discussionmentioning
confidence: 99%
“…Namely, such a sorting provides a very accurate separation of the magnetic phases in the static case as discussed in Ref. 9. It also gives us opportunity to use a moderate number of the hidden layer neurons that is 512 for process classification.…”
Section: Introductionmentioning
confidence: 98%
“…Related to this we expect an even higher fraction of noncollinear ground states, for which the need for calculation of the spin wave dispersions with the more general framework of linear spin wave theory for noncollinear magnets is desired [56,57]. Furthermore, recent developments of machine learning techniques for lattice models and spin Hamiltonians, as for instance a profile method for recognition of three-dimensional magnetic structures [71], determination of phase transition temperatures by means of self-organizing maps [72], and a support vector machines based method for multiclassification of phases [73], will be most useful for identification and classification of competing magnetic phases at finite temperature, and the corresponding phase transition temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…A new paradigm to investigate phase transitions based on neural networks recently emerged. It has been shown that neural networks can classify spin configurations sampled from a Monte Carlo simulation and thus can function as order parameter identifiers 15,16 . The neural network is trained in a supervised fashion, i.e.…”
Section: Introductionmentioning
confidence: 99%